Simulation of water purification using magnetically ultra-responsive micro- and nanoscavengers. (August 2018) - Asghari, E.; Moosavi, A.; Hannani, S.K.
Highlights: Water purification using magnetic particles is investigated numerically. The effects of different parameters on the collection efficiency are determined. By reducing the Reynolds number the collection efficiency increases. An intensive magnetic field is required to collect nanoparticles. Using a baffle a reasonable collection efficiency is achieved for nanoparticles. Abstract: Access to clean water is one of the challenges of the 21st century. Thus water purification is inevitable. One method of water treatment is purification by magnetic particles in the presence of magnetic field. The contaminants are attached to the magnetic particles and then by applying a magnetic field, magnetic particles and, thus, the pollutants can be collected. For the optimal design of a water treatment system, the effect of important parameters in the design, such as magnetic fields, particle size, and Reynolds number are determined numerically by modeling and simulating the water treatment process. Two methods are used to create the magnetic field: permanent magnet and coils. It is shown that there is very little difference in the collection efficiency. Particle size is varied from micrometers to nanometers. In general, the collection efficiency increases by increasing the particle diameter and decreasing the Reynolds number. For example, it is shown that with a magnetic field of strength 0.05 T and Reynolds number of 100, particles with a diameter of 30 micrometers and above are collected completely. However, with decreasing particle diameter to the nanometer, collection efficiency finds a sharp drop. Using baffles to shift the particles toward regions with stronger fields, it is possible to increase the collection efficiency for nanoparticles.